STRATEGI PEMBENTUKAN DISIPLIN BELAJAR DI SANGGAR TARI RADEN KUNING DESA SERI TANJUNG KABUPATEN OGAN ILIR - Yeka Ramadhani; Ardi Saputra; Erna Retna Safitri; Aswasulasikin (STKIP Subang, 2026)
This study aims to investigate the strategies for forming learning discipline at Sanggar Tari Raden Kuning, Seri Tanjung Village, Ogan Ilir Regency. A descriptive qualitative approach was employed. Research subjects consisted of one trainer, two students, and two parents selected through purposive sampling. Data were collected through in-depth interviews, non-participant observation, and documentation. Results indicate that learning discipline formation was implemented through three main strategies based on B.F. Skinner’s behaviorism theory: (1) reinforcement through verbal praise, small rewards, and front-row placement; (2) educational punishment through gentle reprimands and movement repetition; and (3) behavioral conditioning through consistent training routines. The success of these strategies was evidenced by the achievement of four learning discipline indicators: punctuality, compliance with instructions, consistency in practice, and responsibility for movement tasks. Furthermore, cultural values embedded in Tari Gending Sriwijaya, Tari Tanggai, and Tari Zapin Rodat reinforced discipline formation, transforming it from mere external compliance into internal commitment rooted in the nation’s noble cultural values.